2018
DOI: 10.2319/120317-825.1
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between 3D dentofacial photogrammetry measurements and traditional cephalometric measurements

Abstract: Objectives: To determine the relationship between traditional cephalometric measurements and corresponding nonradiographic three-dimensional (3D) photogrammetry measurements. Materials and Methods: This was a cross-sectional study of 20 orthodontic patients (10 male and 10 female) who received lateral cephalometric radiographs and 3D dentofacial photogrammetric records with each subject serving as his or her own control for a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…Over the past decade, advancements in virtual reality techniques, computer-enhanced technologies, cone-beam computed tomography (CBCT), and many others have significantly improved overall dental treatment. Today, 3D cephalometric measurements, 3D virtual treatment planning for skeletal, facial, jaw/bone, and teeth measurements, along with detailed 3D studies of superficial, skeletal, and skin anatomy, appear to greatly enhance success rates and reduce the occurrence of troublesome complications or limitations in treatment algorithms [62][63][64][65][66]. Despite the advancements and improvements in new techniques, it is always important to consider the potential for human and computer errors.…”
Section: Discussionmentioning
confidence: 99%
“…Over the past decade, advancements in virtual reality techniques, computer-enhanced technologies, cone-beam computed tomography (CBCT), and many others have significantly improved overall dental treatment. Today, 3D cephalometric measurements, 3D virtual treatment planning for skeletal, facial, jaw/bone, and teeth measurements, along with detailed 3D studies of superficial, skeletal, and skin anatomy, appear to greatly enhance success rates and reduce the occurrence of troublesome complications or limitations in treatment algorithms [62][63][64][65][66]. Despite the advancements and improvements in new techniques, it is always important to consider the potential for human and computer errors.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, after a certain stage of accumulation of factual material, in our opinion, it is extremely important not only to determine the limits of normative values of cranio-and gnatometric indicators of teleroentgenograms but also to model appropriate indicators characteristic of certain groups of the population. This is logical, the numerous publications on the presence of correlations between different cephalometric indicators, both foreign [5,11,15] and domestic researchers [1,4] are given.…”
Section: Relevancementioning
confidence: 99%
“…In addition, after a certain stage of accumulation of factual material, in our opinion, it is extremely important not only to determine the limits of normative values of cranio-and gnatometric indicators of teleroentgenograms but also to model appropriate indicators characteristic of certain groups of the population. This is logical, the numerous publications on the presence of correlations between different cephalometric indicators, both foreign [5,11,15] and domestic researchers [1,4] are given.The aim of the work is to build and analyze regression models of tele-teleroentgenographic indicators, which can be adjusted during surgery depending on the parameters that usually do not change in Ukrainian young men and young women with different facial profiles according to Schwarz A. M. with normal occlusion close to orthognathic occlusion and a harmonious face.…”
mentioning
confidence: 99%
“…Juerchott et al investigated the reliability of 3D cephalometric landmarks traced on magnetic resonance imaging (MRI) records [ 7 ]. Catillo et al demonstrated that jaws relation and incisors orientation could be predicted from 3D photogrammetry measurements [ 8 ].…”
Section: Introductionmentioning
confidence: 99%